БЕЗТРАНСФОРМАТОРНИЙ ПІДВИЩУЮЧИЙ ПЕРЕТВОРЮВАЧ ПОСТІЙНОЇ НАПРУГИ ДЛЯ ВІДНОВЛЮВАНИХ ДЖЕРЕЛ ЕНЕРГІЇ - Войтех, В.О. (Інститут електродинаміки Національної академії наук України, 2017)
Photovoltaic panels scheme and electrical characteristics have showed, advantages and disadvantages serial panels connection and use of separate microinverter for each panel have considered. Boost-converter for renewable energy scheme, the working principles, mathematical equations and expressions for calculation of  inductance and capacitance have presented. Analysis of iron powder, sendust and ferrite  using as materials for inductor core and their electrical characteristics have made, the  calculation results for boost-converter inductor with the number of photovoltaic panels to 10 have showed. References 4, figures 7, table.